Where is the “Global South” located in scientific research? - Pierre Mazzega; Devi M. Rugmini; Ana Flávia Barros-Platiau (Earth System Governance)
Although the term “Global South” has been increasingly invoked by heads of State as a call for enhanced multilateralism and institutional reform, its academic conceptualization remains underdeveloped. Therefore, we investigate how and where scientific knowledge about the Global South is produced, using a meta-analysis of around 17,000 articles [1994–2024] indexed in Scopus database. The paper shows that authors and funding are predominantly from Global North institutions, particularly the United States. However, rising powers are increasingly active contributors, notably South Africa, India, China and Brazil. The most frequent research topics include globalization, COVID-19, climate change, gender issues, neoliberalism, decolonization and sustainability. The results also reveal the centrality of Africa in the debate, and the underrepresentation of Global South institutions in leading journals. The conclusion calls for more scientific collaboration to improve visibility of knowledge produced in the Global South institutions and suggests that ESG may be a key player.